Iodine-125 Seeds Inhibit Carcinogenesis of Hepatocellular Carcinoma Cells by Suppressing Epithelial-Mesenchymal Transition via TGF-β1/Smad Signaling - Chongshuang Yang (Disease Markers, 2022)
To investigate the radioactive iodine-125 (I-125) seed on migrating and invading of hepatocellular carcinoma (HCC) cells and its mechanism, the irradiation of PLC and Huh7 cells was carried out with I-125 seeds in vitro. Cell counting kit 8 assay was employed to measure cell viability. Cell migration was evaluated by using wound-healing assay. Cell invasion was detected by Transwell assay; RT-PCR and Western blot were used for the detection of the mRNA and proteins of TGF-β1 signaling pathway-related genes. The viability of PLC and Huh7 cells declined in a dose-dependent manner with increasing irradiation from 0 Gy, 2 Gy, 4 Gy, and 6 Gy, to 8 Gy, respectively. The IC50 of PLC and Huh7 cells were 6.20 Gy and 5.39 Gy, respectively, after 24 h of irradiation. Migration and invasion abilities of I-125 group cells were greatly weakened (P<0.05) comparing with the control group. According to the outcomes of RT-PCR and WB, I-125 seed irradiation significantly inhibited the mRNA and protein expression of N-cadherin, vimentin, TGF-β1, p-Smad2/3, and Snail. But the mRNA and protein expressions of E-cadherin were enhanced. Rescue experiment demonstrates that TGF-β1 activator could reverse the inhibitory effects of I-125 on invasion and migration of cells. The results of in vivo experiments further verified that the I-125 seeds can inhibit the proliferation and TGF-β1 of xenographed PLC cells. In conclusion, I-125 seeds restrain the invasion and migration of HCC cells by suppressing epithelial to mesenchymal transition, which may associate with the inhibition of the TGF-β1 signaling.